Cultural Literacy Learning to Improve Elementary School Students' Understanding of Local Culture - Mursalim; Desti Rahayu; Alman; Ahmad Yulianto; Asrul (Jurnal Ilmiah Sekolah Dasar, 2026)
Cultural literacy-based learning plays an essential role in primary education as it fosters students’ understanding of local cultural values, practices, and identity. This study aims to analyze the effect of cultural literacy learning on improving elementary students’ understanding of local culture. The study used a quantitative method with a pretest–posttest control group quasi-experimental design, involved 62 fifth-grade elementary school students. The experimental group received cultural literacy-based learning, while the control group followed conventional instruction. The research instrument consisted of five essay items that were validated by experts and tested empirically, with reliability confirmed through a Cronbach’s Alpha value of 0.74. Data were analyzed using the Shapiro-Wilk test, independent samples t-test, and N-gain analysis. The findings indicate that both groups experienced an improvement in their understanding of local culture; however, the increase in the experimental group was substantially higher. The average score of the experimental group rose from 74.5 on the pretest to 91.4 on the posttest, while the control group increased from 68.2 to 76.5. The independent samples t-test produced a significance value of 0.000 (p < 0.05), confirming a significant difference between the two groups. The N-gain score of 0.77 (high category) further demonstrates that cultural literacy learning was more effective than conventional methods in enhancing students’ cultural understanding.